Simulation of emissions from pottery kilns in the Roman period - Clemens Drüe (Meteorological Applications)
Abstract Present‐day air quality is known through dense monitoring and extensive pollution control mechanisms. In contrast, knowledge of historical pollution, particularly before the industrial revolution, is accessible only through occasional reports of singular local events and through natural archives such as ice or sediment cores that record global‐scale pollution. However, the regular local to regional pollution that most affects human life is hardly known. Historical sciences have argued both for and against significant air pollution in and around historic cities and manufacturing sites. For the Roman era, it has been hypothesized that air quality played a role in several patterns of action of the period. However, to the author's knowledge, there are no quantitative studies of Roman emissions. Using the results of modern experimental archaeology, this study attempts to quantify the emissions from Roman pottery kilns and their impact on surrounding human settlements. It is shown that although the pollution did not reach today's limits, it must have approached levels known to cause adverse health effects. A series of additional test simulations have been conducted to determine how these first results might be improved in the future.